Simulation of the Propagation of Circumferential Crack in the Cylindrical Element Structure Exposed to Cyclic Loadings - Melezhyk, Irina Ivanovna; Shulzhenko, Nikolay Grigor'evich; Garmash, Nataliya Grigor'evna; Gontarovskiy, Pavel Petrovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2018)
The purpose of these studies was to work out the methodsfor the computation of crack development in the plate and axisymmetric elements of structures at cyclic loading for the plasto-elastic arrangement using the conception of the accumulation of scattered damages in the material. In the domain in question, we simulated the processes of alternating-sign plasto-elastic deformation and the material crack resistance was estimated using the fatigue test data for smooth specimens. Thermal and elastically-deformed states of the structure were determined for different loading modes using the finite elements method. The material damageability was assessed for the curves of low-cycle fatigue and for the range of plasto-elastic deformations on the route of probable crack propagation using the hypothesis of linear summation. As soon as a critical value of the damageability is achieved the crack is propagated stepwise for the specified step. As an example, consideration was given to the kinetics of circumferential crack in the cylindrical element exposed to the axial-symmetric cyclic loading. The contact of crack edges was taken into consideration for compressing loading semicycles. The obtained data agree with the data obtained using the Newman method. The suggested technique can be used for the estimation of survivability of the elements of steam turbines (heat rotor grooves at start-up-stop modes, blade and disk interlocks, etc.).